Pengelompokan Daerah Penyebaran Demam Berdarah Dengue Alam Dengan Menggunakan Algoritma K-Means Di Kota Makassar - Zulkifli Rais; Misveria Villa Waru (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2021)
This study proposes the k-means method to map the endemic areas of dengue fever in the city of Makassar. Data were obtained from the health department based on the number of patients affected by dengue hemorrhagic fever (DHF) in every sub-district in Makassar City. The k-means method has mapped the area into 3 groups. These results indicate that group 1, which is the area that has the highest number of DHF sufferers, is Rappocini, Panakukang, and Manggala villages. Furthermore, Tamalate and Biringkanaya villages are members of group 2. And group 3 is an area that has a low number of dengue patients, namely Mamajang, Makassar, Tamalanrea, Mariso, Ujung Pandang, Bontoala, Tallo, Ujung Tanah, Wajo. Keywords: k-means, dengue hemorrhagic fever (DHF)